Methodological support for managing of critical competences in Agile transformation projects within a multi-project medical environment - Dotsenko, Nataliia; Chumachenko, Igor; Kraivskyi, Bohdan; Railian, Maryna; Litvinov, Anatoly (Національний технічний університет "Харківський політехнічний інститут", 2024)
Ensuring the continuity, efficiency and quality of medical care requires solving the problem of managing the critical competencies of personnel in a multi-project medical environment. The object of research is resource management processes in the medical environment. The subject of the research is models, methods and processes of managing critical competencies in Agile projects of transformation of a multi-project medical environment. The purpose of the work is to develop methodological support for managing critical competencies in Agile transformation projects within a multi-project medical environment. The article addresses the following tasks: analysis of factors affecting the formation of the register of critical competencies in the medical environment; development of a conceptual model for critical competence management; development of an aggregated model for the configuration management process of critical competencies; development of a method for managing critical competencies; development of recommendations for applying of methodological support for managing critical competencies in Agile transformation projects within a multi-project medical environment.

Забезпечення безперервності, оперативності та якості надання медичної допомоги потребує вирішення задачі управління критичними компетенціями персоналу мультипроєктного медичного середовища. Об’єктом дослідженняє процеси управління ресурсами в медичному середовищі. Предметом дослідженняє моделі, методи та процеси управління критичними компетенціями в проєктах Agile трансформації мультипроєктного медичного середовища. Метою роботиє розробка методологічного забезпечення управління критичними компетенціями в проєктах Agile трансформації мультипроєктного медичного середовища. У статті вирішуються завдання: аналіз чинників, що впливають на формування реєстру критичних компетенцій в медичному середовищі; розробка концептуальної моделі управління критичними компетенціями; розробка агрегованої моделі процесу конфігураційного управління критичними компетенціями; розробка метод управління критичними компетенціями; розробка рекомендацій з застосування методологічного забезпечення управління критичними компетенціями впроєктах Agile трансформації мультипроєктного медичного середовища.
Методологічне забезпечення управління критичними компетенціями в проєктах Agile трансформації мультипроєктного медичного середовища
Keywords: project management; critical competencies; human resources; Agile transformation; configuration management; управління проєктами; критичні компетенції; людські ресурси; Agile трансформація; конфігураційне управління